(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
In order for the performance improvement strategy to be successful, the company needs to know the performance targets. Factors that can affect employee performance include communication, motivation and teamwork. The purpose of this study was to determine the effect of communication, motivation and teamwork on employee performance at PT. Cocoa Bali Pods. All members of the population are involved as respondents using the census method. The data analysis technique used is multiple linear regression analysis. The results of the partial significance test prove that communication, motivation and teamwork have a positive and significant effect on employee performance. Simultaneous test results prove that communication, motivation and teamwork have a positive and significant effect on employee performance. The suggestions given include overcoming problems that occur due to conflicts in the work environment and increasing cooperation between employees by preventing blaming one another.